Analisis Ketersediaan Obat dan DampaknyaTterhadap Pasien di Instalasi Farmasi RSUD Elia Waran Manokwari Selatan Tahun 2024 - Andriyanto, Dwi Ris; Windiyaningsih, Cicilia; Garnida, Aliefety Putu (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2025)
Background: Pharmaceutical services are both a supporting service and a major revenue center. According to the 2023 year-end report from the Pharmacy Installation of Elia Waran General Hospital, several issues regarding drug availability were identified from January to December 2023. These issues include suboptimal drug needs planning, the absence of a formulary, a high number of drugs not being dispensed, and expired medications being found in the hospital. Method: This research employs a qualitative approach with operational research. The qualitative research design includes in-depth interviews, document reviews, and observations. The study was conducted at Elia Waran General Hospital from May to June 2024. Primary data was obtained from structured interviews with several respondents and direct observations of the drug management process. Secondary data was collected from documents available at the hospital’s pharmacy installation, including data on drug management processes in 2023, scientific journals, laws and regulations, books, and various relevant research findings. Results: The results indicate that in terms of input and process, some pharmaceutical service indicators have not yet reached 100%, such as the improvement of drug availability, which has not been maximally implemented by pharmaceutical staff. The pharmaceutical service standards at RSUD Elia Waran are relatively adequate, and policies regarding pharmaceutical service standards have been established based on Minister of Health Regulation Number 72 of 2016. Conclusion:Elia Waran General Hospital has implemented the provisions of Minister of Health Regulation Number 72 of 2016, although some indicators have not yet been achieved. Therefore, further evaluations should be conducted to identify areas that need improvement or restructuring, and there should be a socialization effort to enhance awareness regarding pharmaceutical services.